The impact of the COVID‐19 pandemic on internal migration in Germany: A descriptive analysis. Issue 6 (29th March 2022) - Stawarz, Nico; Rosenbaum‐Feldbrügge, Matthias; Sander, Nikola; Sulak, Harun; Knobloch, Vanessa
Abstract: The COVID‐19 pandemic has affected economies, labor markets, health care, education and tourism around the globe in unprecedented ways. However, little research has yet been devoted to the impact that the pandemic might have had on internal migration. This study aims to address this gap by determining how the intensity and spatial patterns of internal migration changed between 2019 and 2020 in Germany. We draw on data from the population register on annual flows between 401 counties. We find that the COVID‐19 pandemic was associated with a 5% drop in the intensity of inter‐county migration in 2020 compared to the previous year, with significant variation across age. The pandemic was also associated with an upsurge in net migration losses for the largest cities, driven by fewer inflows of young adults and continuing outflows of families.